(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The intensification of the struggle for the consumer in the conditions of economic instability and digital transformation requires the search for optimal solutions to ensure competitiveness, marketing personalization and efficiency of business processes in retail. The purpose of the article is to analyze the marketing wars of the largest FMCG retail chains in Ukraine and determine the role of modern information technologies in the competitive struggle. Methods. The use of methods of analysis, comparison and theoretical generalization allowed us to investigate the features of the application of marketing promotion methods and obtaining competitive advantages in the field of food retail. Results. The article compares the main players in the Ukrainian grocery retail market, promotional offers, positioning of own brands, and describes the use of information technologies in LLC «ATB-market» and LLC «Silpo-Food». Conclusions. It has been established that LLC "ATB-Market" and LLC "Silpo-Food" use conceptually different approaches to the formation of marketing strategies and the use of modern information technologies in the field of FMCG retail. LLC «ATB-Market» emphasizes scale, accessibility and operational efficiency, LLC «Silpo-Food» builds loyalty through emotional customer experience and innovative service.